Influence of the use of the dung of cow on the compressive strength of mortars of bar ground - HOUEHANOU, ERNESTO CABRAL; TANKPINOU ÉPOUSE KIKI, YVETTE SÈDJRO; DJOSSOU, A. D.; HOUNGAN, COMLAN ARISTIDE; DEGAN, GÉRARD; GBAGUIDI AÏSSE, GÉRARD LÉOPOLD (My University, 2017)
The use of the materials of proximity is imperative more and more in the traditional constructions and the house in rural areas. In numerous traditions, the dung of cow (DOC) is a basic material in the construction. However, the performances of the use of the dung of cow (DOC) in the construction are scientifically little proved. The present research project studied the influence of the use of the dung of cow on the compressive strength of mortars of bar ground for the usages of blocks in compressed ground (BCG) and/or blocks in stabilized ground (BSG). An analysis is led by comparing the compressive strength of reference mortars (simple bar ground and bar ground more 4 %, 8 % and 12 % of Portland cement) and mortars (simple bar ground and cement Portland) containing different proportions of BDV (2 %, 4 %, 6 %, 8 % and 10 %). The results mainly allowed to show that the addition of a small quantity (lower than 6 %) of DOC sawdust doesn’t decrease the compressive strength of the mortar of bar ground, it tends to improve it slightly. Beyond a 6 % content, the addition of the DOC decreases systematically the compressive strength of the mortar of bar ground.
Keywords: Bar ground; stabilized; dung of cow; compressive strength